Management of Hyperemesis Gravidarum Using Steroid Therapy - Sadaf Tufail, Farzana Kazmi, Sobia Nawaz, Maliha Sadaf, Farah Rehana , (Journal of Rawalpindi Medical College, 2012)
Background: To compare the efficacy of short course of steroid with dimenhydrinate (antihistamine) in the treatment of intractable hyperemesis gravidarum. Methods: In this descriptive study fifty patients were assigned to receive intravenous hydrocortisone 100 mg eight hourly as a daily dose for three days.Subsequently, oral prednisolone 45 mg which was tapered off in 5 days. Fifty patients were given intravenous dimenhydrinate 50 mg 3 times daily for 3 days, followed by oral tablets of 50mg three times a day for 5 days . Patients were followed up daily during the therapy course and for 2 wks following discharge . Results: There was a significant reduction in vomiting episodes in the hydrocortisone group compared with the dimenhydrinate group (p < .0001). None of the patient from the hydrocortisone group but eight of the patients receiving dimenhydrinate were readmitted for intractable vomiting within 1 wk after discharge. . Conclusion: Short corticosteroids’ course is an effective treatment for intractable hyperemesis gravidarum.